PENGGUNAAN MODEL PROBLEM BASED LEARNING ( PBL ) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 04 BARIANG RAO – RAO KABUPATEN SOLOK SELATAN - Fauzana, Ulfa; Muhammadi, Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the use of the Problem Based Learning (PBL) Model to Improve Student Learning Outcomes in Pancasila Education Learning in Class V SDN 04 Bariang Rao - Rao, South Solok Regency. This type of research is Classroom Action Research (PTK). The research results showed an increase in the teaching modules for cycle I 83.33% (Good) and cycle II 95.83% (Very Good). The first cycle teacher activity assessment was 82.14% (Good) and the second cycle teacher activity assessment was 92.85% (Very Good). Assessment of students in improving learning outcomes in cycle I was 82.14% and cycle II was 92.85%. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in learning Pancasila Education in class V.